Evolving management of colorectal polyps. (September 2021) - Ichkhanian, Yervant; Zuchelli, Tobias; Watson, Andrew; Piraka, Cyrus
Advances in endoscopic technology have led to increased success in colorectal cancer (CRC) screening and polyp management, with reduction of CRC incidence and mortality. Despite these advances, CRC is still one of the leading causes of cancer deaths, and half of all CRC develops from lesions that were missed during colonoscopy while one-fifth of CRC arise from prior incomplete resection. Techniques to improve polyp detection are needed, along with optimization of complete resection of any abnormal lesions that are found. This article will review the currently available endoscopic resection techniques and will discuss where they fit in the management of polyps of different sizes and types, such as pedunculated versus nonpedunculated, and those with or without suspected invasion.